Comparative Study of Bioactive Compounds of Several Varieties of Sembalun Garlic, Lombok, West Nusa Tenggara - Ishmah Humaidatul Amini Zaim Alyaminy; Atika, Baiq Naili Dewi; Khaerul Ihwan; Pahmi Husain; Dwi Kartika Risfianty; Irna Il Sanuriza; Irfan Jayadi (Jurnal Biologi Tropis, 2024)
Indonesia is known as a rich country in herbs, which are utilized as a source of natural herbal medicine, including garlic. This research aims to achieve a comparative study of the bioactive compounds retained in several varieties of Sembalun garlic. The research was conducted at the Integrated Laboratory of Mataram State Islamic University and Laboratory of Biology, Faculty of Mathematics and Natural Sciences, University of Nahdlatul Wathan Mataram. Three varieties of Sembalun Garlic were used in this research, namely the Nunggal, Jamak and Sanggah varieties, which were extracted using 96% ethanol. The research results show bioactive compounds in flavonoids, saponins, steroids and phenolics in the three varieties of Sembalun garlic (Nunggal, Jamak, and Sanggah).